The effects of collaborative versus individual writing on fluency, complexity and accuracy among refugee learners / Jessica Thevamalar Rummy@ Henry - Jessica Thevamalar , Rummy@ Henry (2018)
Researchers are focusing more on the writing component especially on the impact of collaborative writing tasks on writing performances as compared to individual writing tasks. The study is grounded on Vygotsky’s sociocultural theory of mind (1978) that posits social interactions among learners are important for the “input” in second language learning. In pursuit of having a new perspective in types of suitable assessments for writing in the educational system for learners, it is important to identify and assess the needs of learners from marginalized backgrounds that have been deprived of basic education. Refugee children and children of asylum seekers in countries of first asylum like Malaysia often face difficulties in having quality education and their education needs are a challenge among researchers and education practitioners. The aims of the study are to compare collaborative and individual writting tasks in order to identify the differences in the level of fluency, complexity and accuracy, to explore the effectiveness of collaborative and individual writing tasks on the writing performances, followed by to examine the focus of language related episodes (LREs) among paired learners and finally on the learners’ approach towards the writing tasks. This study will provide an insight to educators handling the education of refugee learners with potential new ideas to enhance learners’ writing skills and assist them to prepare effective writing tasks for their learners. The findings of the study showed that collaborative writing tasks have positive effect on the accuracy of written texts produced. However, collaboratively written texts were relatively shorter in length and disorganized in terms of ideas and supporting details. Meanwhile, the collaborative dialogue provided a platform for learners to discuss, contribute inputs, give opinions and correctly resolve the utterances for a better writing output, as evident in the language related episodes (LREs). The present study suggests that teachers and administrators to spend some time teaching students the concept of collaboration and the benefits of learning together before giving them collaborative writing tasks.